Factors Associated with Decision Making Capacity in Older Adults - CORRIGAN, MARIA (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2019)
Abstract: Making our own decisions goes to the heart of our autonomy. Increasingly decision making capacity (DMC) of older adults is questioned. The aim of this study was to explore DMC in older people and examine for associations between decision making abilities and factors not previously explored, including cognitive reserve (CR) and participation in decision making. Data were collected for two groups of 29 participants (16 Females and 13 Males), aged between 56 years and 90 years, (M=73.8years, SD=9.6). Group One (n=15) was older adults at low risk of impaired DMC, (i.e. without clinical diagnosis and not receiving support). Group Two (n=12) was older adults at increased risk of impaired decision making capacity, (i.e. with clinical diagnosis or requiring support). A semi structured interview and ACED, LEQ, WASI and DRS assessments were administered for each. These yielded data regarding decision making abilities (health and finance domains), CR, cognitive functioning and preference/participation in decision making. Statistically significant positive relationships were observed between decision making abilities and CR (rs=0.45, p < 0.05; rs=0.61, p < 0.05) and between decision making abilities and participation in decision making (rs=0.69, p < 0.05; rs=0.65, p < 0.05). Results suggested that DMC models may be informed further by consideration of CR and life experiences, such as participation in decision making. This may contribute to explanations for DMC variances and to supports and opportunities provided by services to individuals over their life span. Limitations of the study, including the small number of participants are discussed. Further study is required. New research avenues are suggested including systematic evaluation of provision of structured decision making opportunities.
APPROVED
Keywords: Older Adults; Cognitive Reserve; Participation in Decision Making; Preference re Decision Making; Adults at risk of impaired DMC; Cognitive Functioning; Everyday Decision Making; Decision Making Capacity; ACED